Protective Effects of Oroxylin A on Retinal Ganglion Cells in Experimental Model of Anterior Ischemic Optic Neuropathy - Jia-Ying Chien; Shu-Fang Lin; Yu-Yau Chou; Chi-Ying F. Huang; Shun-Ping Huang (MDPI AG, 2021)
Nonarteritic anterior ischemic optic neuropathy (NAION) is the most common cause of acute vision loss in older people, and there is no effective therapy. The effect of the systemic or local application of steroids for NAION patients remains controversial. Oroxylin A (OA) (5,7-dihydroxy-6-methoxyflavone) is a bioactive flavonoid extracted from Scutellariae baicalensis Georgi. with various beneficial effects, including anti-inflammatory and neuroprotective effects. A previous study showed that OA promotes retinal ganglion cell (RGC) survival after optic nerve (ON) crush injury. The purpose of this research was to further explore the potential actions of OA in ischemic injury in an experimental anterior ischemic optic neuropathy (rAION) rat model induced by photothrombosis. Our results show that OA efficiently attenuated ischemic injury in rats by reducing optic disc edema, the apoptotic death of retinal ganglion cells, and the infiltration of inflammatory cells. Moreover, OA significantly ameliorated the pathologic changes of demyelination, modulated microglial polarization, and preserved visual function after rAION induction. OA activated nuclear factor E2 related factor (Nrf2) signaling and its downstream antioxidant enzymes NAD(P)H:quinone oxidoreductase (NQO-1) and heme oxygenase 1 (HO-1) in the retina. We demonstrated that OA activates Nrf2 signaling, protecting retinal ganglion cells from ischemic injury, in the rAION model and could potentially be used as a therapeutic approach in ischemic optic neuropathy.